Political and Cultural Mobilisation of Lithuanian Women in the USA at the End of the 19th Century – Beginning of the 20th Century - Navickaitė, Marija (History / Istorija, 2024)
Abstract. Between 1899 and the First World War alone, more than 250,000 Lithuanians came to the United States, almost 82,000 of whom were women. Emigration led to the rapid education and emancipation of women in the United States. Women rapidly began to join public organisations, express themselves in educational, cultural activities, in the press, where the position of women was formed and the voice of women was highlighted. However, the voice, political and cultural emancipation of Lithuanian women has not received more attention from researchers. Women’s activity in the U.S. still remains on the margins. Based on sparse historiography and published sources (mainly Lithuanian periodicals in the USA) the aim of this article is to present the general characteristics of the political and cultural self-perception of Lithuanian women in the United States at the end of the 19th century and the beginning of the 20th century.